The use of public spatial databases in risk analysis: A US‐oriented tutorial - Greenberg, Michael R.; Schneider, Dona; Cox, Louis Anthony (Risk analysis, 2025)
This tutorial focuses on opportunities and challenges associated with using six large, publicly accessible spatial databases published during the last decade by US federal agencies. These databases provide opportunities for researchers to risk‐inform policy by comparing community asset, demographic, economic, and social data, along with anthropogenic and natural hazard data at multiple geographic scales. The opportunities for data analysis come with challenges, including data accuracy, variations in the shape and size of data cells, spatial autocorrelation, and other issues endemic to spatial datasets. If ignored, these issues can lead to misleading results. This article briefly reviews the six databases and how agencies use them. It then focuses on the data and its limitations. Examples are provided, as are summaries of the debates surrounding these databases, followed by paths forward for improving their use. We end with a checklist that users should consider when they access any of the six spatial databases or others. We believe that these new resources can be effectively used with appropriate caution to answer user‐generated questions about hazards and risks—questions that are important to both community groups and government decision‐makers.